A Social-Ecological Localised Agriculture Strategy to Enhance Dryland Farming Productivity in Lombok - Ramli Akhmad; Muhammad Okta Ridha Maulidan; Andri Estining Sejati (Lembaga Bale Literasi, 2025)
Agricultural productivity plays a crucial role in ensuring global food security, yet prolonged drought continues to threaten the sustainability of dryland farming systems, particularly in developing countries. This study aims to develop a Localised Agriculture Strategy (LAS) within a Social-Ecological Systems framework to enhance dryland farming productivity in Indonesia. Employing a qualitative case study approach, primary data were collected through observations and in-depth interviews with 16 informants, including farmers, water user groups, and irrigation managers, while secondary data were obtained from relevant documentation. The data were analysed thematically to identify context-specific adaptive strategies. The findings reveal that LAS emerges as a social-ecological adaptation shaped by the interaction between local communities and environmental constraints. Four key strategies were identified: (1) classification of agricultural vulnerability levels based on Awiq-awiq (customary regulations), (2) utilisation of the Rowot Sasak calendar and dryland distribution maps as sources of drought-related information, (3) adjustment of the gogo (upland rice) cultivation system according to drought intensity, and (4) strengthening collective action (gotong royong) in optimising embung (small reservoirs) for irrigation and aligning cropping patterns with water availability. These strategies demonstrate that integrating local knowledge, social institutions, and ecological conditions can significantly improve agricultural productivity in drought-prone areas. This study contributes to the development of social-ecological-based agricultural strategies and offers practical insights for promoting adaptive farming practices and sustainable watershed management in dryland environments.